Three dimensional architecture of the sub epithelial connective tissue in the forestomach of the lesser mouse deer was studied by scanning electron microscopy after macerated with 10% NaOH. In general, the architecture of the connective tissue in the rumen and reticulum showed similar pattern, which was honeycomb like pattern. This pattern was observed in all portions of the forestomach. Primary wall bordered each cell of the honeycomb. Inside the cells there were some secondary or tertiary wall - Savitri Novelina; Srihadi Agungpriyono; Yoshio Yamamoto; Chairun Nisa; Nabuo Kitamura; Junzo Yamada (Media Veteriner, 1999)
Three dimensional architecture of the sub epithelial connective tissue in the forestomach of the lesser mouse deer was studied by scanning electron microscopy after macerated with 10% NaOH. In general, the architecture of the connective tissue in the rumen and reticulum showed similar pattern, which was honeycomb like pattern. This pattern was observed in all portions of the forestomach. Primary wall bordered each cell of the honeycomb. Inside the cells there were some secondary or tertiary wall that connect to the primary ones. The primary wall in the rumen were leaflike shaped with narrow and irregular surface while those of the reticulum were low columnar shaped with convex surface. The honeycomb in the ruminal papillae showed similar pattern from the apical to the basal portion. On the contrary, cone-like primary wall without secondary or tertiary ones dominated the apical portion of the reticulum papillae. The sub epithelial connective tissue consisted of collagen fibers which were arranged and formed a network. The collagen fibers in the rumen were more densely distributed as compared to those of the reticulum. The differences observed may indicate a difference in function between the rumen and the reticulum in the digestive function of the lesser mouse deer.